Mathematica Packages for Solving Schrodinger Equation with One Dimensional Rectangular Potentials - Siddig, Abubaker Ahmed Mohamed (2003)
The determination of eigenvalues and their related eigenfunctions is one of the central problems of quantum mechanics. In this work, the problem of finding energy eigenvalues and eigenfunctions are aptly demonstrated with one dimensional systems of infinite double square well potential, finite double square well potential, rectangular potential hole between two walls and asymmetric square well potential. We develop Mathematica packages for which the Schrodinger equations are solved for each model. The solutions are obtained by graphical and numerical methods in these packages. The packages are easy to use; the user does not need to know the details of the packages in order to use them but the user has a direct control over parameters of the models. Eigenvalues and eigenfunctions have been obtained for various well depths and widths as well as various barrier widths. They are shown to have appropriate limiting solutions. The packages are stable, fast, efficient and can serve as useful tools for teaching systems of one dimensional rectangular potential, in quantum mechanics.